Coopération transfrontalière Brésil/Guyane/Suriname : évolutions et enjeux - Maude Elfort (Confins)
This paper aims to retrace the evolution of Brazil/French Guiana/Surinam cross-border cooperation. Initially focused on questions of border control and surveillance, this cooperation has gradually extended to the economic, social and cultural fields. Through various instruments (Joint Cross-border Commissions, River Councils, INTERREG Amazonia cooperation program), integrating public and private actors operating at different territorial levels, this cooperation aims to promote the process of integration between border territories and contributes to the emergence of a coordinated strategy around the shared development needs of states separated from French Guiana by a common international border.